2017
DOI: 10.1016/j.chom.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The Chlamydia trachomatis Inclusion Membrane Protein CpoS Counteracts STING-Mediated Cellular Surveillance and Suicide Programs

Abstract: Summary Evading cell death is critical for Chlamydia to maintain a replicative niche but the underlying mechanisms are unknown. We screened a library of Chlamydia mutants for modulators of cell death. Inactivation of the inclusion membrane protein CpoS (Chlamydia promoter of Survival) induced rapid apoptotic and necrotic death in infected cells. The protection afforded by CpoS is limited to the inclusion in which it resides indicating that it counteracts a spatially restricted pro-death signal. CpoS-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
167
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(175 citation statements)
references
References 45 publications
7
167
0
1
Order By: Relevance
“…During infection in mammals, bacteria such as Chlamydia generate CDNs that activate the innate immune response in a STING-dependent and cGAS-independent manner (Sixt et al, 2017; Webster et al, 2017). Listeria secretes c-di-AMPs to induce an IFN response that stimulates the STING pathway (Sauer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…During infection in mammals, bacteria such as Chlamydia generate CDNs that activate the innate immune response in a STING-dependent and cGAS-independent manner (Sixt et al, 2017; Webster et al, 2017). Listeria secretes c-di-AMPs to induce an IFN response that stimulates the STING pathway (Sauer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Of 11 Inc mutants examined here, 3 Incs were identified that play a role in mediating vacuolar integrity. A recent study demonstrated that disruption of CT229 (CpoS) leads to host cell death and activiation of the STING pathway (Sixt et al, 2017). The authors propose that this represents a direct effect of CT229 suppressing IFN responses by interfering with membrane-trafficking events to block STING translocation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown if Inc proteins can also act as structural components to bring and maintain the ER and the inclusion membrane in close apposition. C. trachomatis encodes more than 50 putative Incs and only some of them have known functions in C. trachomatis infection (24,28,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Recently, Mirrashidi et al (37) determined the Inc-human interactome from uninfected cells expressing C. trachomatis Inc proteins.…”
mentioning
confidence: 99%